2014
DOI: 10.1002/acr.22189
|View full text |Cite
|
Sign up to set email alerts
|

Who Makes It to the Base? Selection Procedure for a Physical Activity Trial Targeting People With Rheumatoid Arthritis

Abstract: ObjectiveTo compare those who were finally included in a large well-defined sample of individuals with rheumatoid arthritis (RA) at target for a physical activity (PA) trial with those who were not.MethodsIn total, 3,152 individuals answered questionnaires on sociodemographic, disease-related, and psychosocial factors and PA levels. The differences between individuals making it to the baseline assessments and those who did not were analyzed in 3 steps.ResultsIn a first step, 1,932 individuals were eligible for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 47 publications
0
26
0
Order By: Relevance
“…These reasons have been cited in other PA trials in RA 44,45 . An in-depth analysis of participants and nonparticipants in a recent PA trial in RA concluded that only 8% of the initial target population…”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…These reasons have been cited in other PA trials in RA 44,45 . An in-depth analysis of participants and nonparticipants in a recent PA trial in RA concluded that only 8% of the initial target population…”
Section: Discussionmentioning
confidence: 71%
“…Participants who withdrew from a recent PA trial between agreeing to take part and baseline assessment reported more fatigue than those who were assessed (p=0.009) 44 . It is possible that eligible patients who experienced greater fatigue declined participation in studies included in this review and the resulting participants might be less representative of fatigued patients with RA.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations